Impact of plant density on stem diameter, plant height, and branching in hemp (Cannabis sativa L.) - Autumn Brown; Maria Soutor; Shelby Ellison (Agrosystems, Geosciences & Environment)
Abstract Hemp (Cannabis sativa L.) is a dioecious, diploid (2n = 2x = 20), photoperiod‐sensitive crop cultivated worldwide for a variety of uses, including food, feed, medicine, and fiber. Hemp is parsed into different market types, including fiber, grain, dual purpose, and high cannabinoid production. Planting densities for the different market types varies greatly, with fiber production systems planted at a much higher density than those for cannabinoid production. Current recommendations for fiber seeding rates range between 45 and 67 kg per hectare (kg ha−1), with other recommendations reaching 90 kg ha−1. However, few studies have been conducted to determine optimal planting density while considering fiber quality, yield, and input cost. In this study, we used four different planting densities (221 plants m−2, 111 plants m−2, 74 plants m−2 and 55 plants m−2) in a replicated greenhouse trial to study their effect on plant height, stem diameter, and branching. Planting density significantly affected each trait, with a seeding density of 221 plants m−2 producing the thinnest, shortest, and least branched plants. All stem traits were positively correlated with plant height, and stem diameter was the most correlated. A planting density of 111 plants m−2 reduced branching but still produced long, thin stems, translating into a high bast fiber yield while reducing seed input costs and competition between plants.